Nunavut: Canada turns a new page in the Arctic. by John Merrit - Merritt, John. (1993)
tag=1 data=Nunavut: Canada turns a new page in the Arctic. by John Merrit tag=2 data=Merritt, John tag=3 data=Canadian Parliamentary Review, tag=4 data=16 tag=5 data=2 tag=6 data=Summer 1993 tag=7 data=2-8. tag=8 data=ABORIGINAL LAND CLAIMSNADA tag=9 data=INUIT OF NUNAVUT%NUNAVUT FINAL LAND CLAIMS AGREEMENT tag=10 data=In May, 1993 the Prime Minister of Canada and representatives of the Inuit of Nunavut signed the Nunavut Final Land Claims Agreement. tag=11 data=1994/6/1 tag=12 data=94/0001 tag=13 data=CAB In May, 1993 the Prime Minister of Canada and representatives of the Inuit of Nunavut signed the Nunavut Final Land Claims Agreement.